Concurrent variable‐interval variable‐ratio schedules in a dynamic choice environment. Issue 3 (7th November 2017) - Bell, Matthew C.; Baum, William M.
Abstract : Most studies of operant choice have focused on presenting subjects with a fixed pair of schedules across many experimental sessions. Using these methods, studies of concurrent variable‐ interval variable‐ratio schedules helped to evaluate theories of choice. More recently, a growing literature has focused on dynamic choice behavior. Those dynamic choice studies have analyzed behavior on a number of different time scales using concurrent variable‐interval schedules. Following the dynamic choice approach, the present experiment examined performance on concurrent variable‐interval variable‐ratio schedules in a rapidly changing environment. Our objectives were to compare performance on concurrent variable‐interval variable‐ratio schedules with extant data on concurrent variable‐interval variable‐interval schedules using a dynamic choice procedure and to extend earlier work on concurrent variable‐interval variable‐ratio schedules. We analyzed performances at different time scales, finding strong similarities between concurrent variable‐interval variable‐interval and concurrent variable‐interval variable‐ ratio performance within dynamic choice procedures. Time‐based measures revealed almost identical performance in the two procedures compared with response‐based measures, supporting the view that choice is best understood as time allocation. Performance at the smaller time scale of visits accorded with the tendency seen in earlier research toward developing a pattern of strong preference for and long visits to the richer alternative paired with brief "samples" at the leaner alternative ("fix and sample").